The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jsfa.6789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light quality on the accumulation of phytochemicals in vegetables produced in controlled environments: a review

Abstract: Phytochemicals in vegetables are important for human health, and their biosynthesis, metabolism and accumulation are affected by environmental factors. Light condition (light quality, light intensity and photoperiod) is one of the most important environmental variables in regulating vegetable growth, development and phytochemical accumulation, particularly for vegetables produced in controlled environments. With the development of light-emitting diode (LED) technology, the regulation of light environments has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
224
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(267 citation statements)
references
References 128 publications
4
224
2
9
Order By: Relevance
“…Cytokinins are associated with the stimulation of phenolic compound synthesis (Jeong et al, 2007;Lee et al, 2010). Although green light may be related to the growth and synthesis of endogenous substances via cryptochrome-dependent and independent mechanisms (Folta and Childers, 2008;Bian et al, 2015). In the present study, the fresh and dry weight of the seedlings exposed to green light were lower than those of the seedlings treated under othonianum Rizz.…”
Section: Discussioncontrasting
confidence: 51%
“…Cytokinins are associated with the stimulation of phenolic compound synthesis (Jeong et al, 2007;Lee et al, 2010). Although green light may be related to the growth and synthesis of endogenous substances via cryptochrome-dependent and independent mechanisms (Folta and Childers, 2008;Bian et al, 2015). In the present study, the fresh and dry weight of the seedlings exposed to green light were lower than those of the seedlings treated under othonianum Rizz.…”
Section: Discussioncontrasting
confidence: 51%
“…The unfolding which was carried out for the interaction found in internal °hue, demonstrated that the colors did not influence its value in cultivar Albion, however, for Camarosa, the blue cover provided lower °hue (more intense color). Considering that the authors obtained fruits with more intense and darker color under the blue cover, it is possible that blue light, which is characterized by being more energetic, could have caused the browning of the fruits through degradation of the cells or due to promote stimulation of synthesis of anthocyanin, which acts as a photoprotector and gives the characteristic red color (Bian et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Plant development is strongly influenced by light quality, which refers to the composition of spectrum or wavelengths reaching a plant (Johkan et al, 2010;Bian et al, 2015). Red and blue lights have the greatest impact on plant growth because they are the major energy sources for CO2 assimilation in plant.…”
Section: Introductionmentioning
confidence: 99%